Effects of urea-N and CO2 coupling fertilization on the growth, photosynthesis, yield and anthocyanin content of hydroponic purple cabbage Brassica campestris ssp. chinensis - Chen, Danyan; Feng, Yuanyuan; Liu, Ya; Hu, Juan; Li, Shilong; Ma, Jingze; Lu, Xinyu; Jiang, Xiaorui; Sun, Shuhui; Yang, Zhi; et al. (International Journal of Agricultural and Biological Engineering, 2023)
Water and fertilizer coupling is a high-efficiency technology for the development of facility agriculture. However, the interaction effect of nitrogen (N) and air carbon dioxide (CO2) on hydroponic purple cabbage, especially on its leaf anthocyanins under hydroponic solution systems, remains unexplored. In this study, six treatments were set as C0N0, C0N2, C0N4, C1N0, C1N2 and C1N4, with N0, N2 and N4 being 0.0 g/L, 0.2 g/L and 0.4 g/L exogenous urea-N to hydroponic solution dilution, respectively. C0 and C1 were set as with and without CO2 fertilizer (i.e., 800 g CO2 agent added one week after transplanting and 600 g CO2 agent added when the plant reached 15 cm in height), respectively. Pot experiments were conducted to investigate the interaction effect of N and air CO2 (N×CO2) on the growth, photosynthesis, yield and anthocyanin content of hydroponic purple cabbage Brassica campestris ssp. chinensis. The results showed N×CO2 extremely significantly influenced plant height (H), net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular oxidation concentration (Ci), transpiration rate (Tr), leaf water use efficiency (LWUE) and yield. The C1N0 treatment had the largest yield at 262.5 g/plant, with higher values for root length, root weight, plant height and leaf number than the other treatments. The Pn, Ci and Tr of C1N4 were the highest at 3.05 μmol CO2/m2•s, 352.8 μmol CO2/m2•s and 2.31 mmol H2O/m2•s, respectively. The C1N2 treatment received the largest Gs value of 0.70 mol H2O/m2•s and the largest Tr of 2.31 mmol H2O/m2•s. There was the highest LWUE for C0N2 (1.41) and the highest anthocyanin content for C1N2 (1.35 mg/kg). There was a significant negative correlation between leaf number and anthocyanin (r = –0.414, p<0.05). The findings demonstrated that adding CO2 fertilizer and 0.2 g/L exogenous urea-N to hydroponic solution dilution is a potential N×CO2 coupling strategy to increase anthocyanin and the yield of purple cabbage. Keywords: nitrogen concentration, carbon dioxide, purple cabbage, hydroponic solution, anthocyanins DOI: 10.25165/j.ijabe.20231605.7638 Citation: Chen D Y, Feng Y Y, Liu Y, Hu J, Li S L, Ma J Z, et al. Effects of urea-N and CO2 coupling fertilization on the growth, photosynthesis, yield and anthocyanin content of hydroponic purple cabbage Brassica campestris ssp. chinensis. Int J Agric & Biol Eng, 2023; 16(5): 123–131.